Assessing the energy demand reduction in a surgical suite by optimizing the HVAC operation during off-use periods - Cacabelos, Antón; López-González, José Luis; González-Gil, Arturo; Febrero-Garrido, Lara; Eguía-Oller, Pablo; Granada-Álvarez, Enrique (Applied Sciences (Switzerland), 2020)
Hospital surgical suites are high consumers of energy due to the strict indoor air quality (IAQ) conditions. However, by varying the ventilation strategies, the potential for energy savings is great, particularly during periods without activity. In addition, there is no international consensus on the ventilation and hygrothermal requirements for surgical areas. In this work, a dynamic energy model of a surgical suite of a Spanish hospital is developed. This energy model is calibrated and validated with experimental data collected during real operation. The model is used to simulate the yearly energy performance of the surgical suite under different ventilation scenarios. The common issue in the studied ventilation strategies is that the hygrothermal conditions ranges are extended during off-use hours. The maximum savings obtained are around 70% of the energy demand without compromising the safety and health of patients and medical staff, as the study complies with current heating, ventilation and air conditioning (HVAC) regulations.